The Evaluatıon Of The Symmetry And Norms Of Upperface, Mıdface And Lowerface By Basılar Cephalometrıc Analysıs Method - Yalçın Işımer (Galenos Yayinevi, 1991)
In this present study, a sample of 20 male adults with skeletal Class I relationship was selected. Basiler radiographies were obtained from each subject. None of them showed and facial asymmetry and malocclusion. The evaluation of head and facial structures was investigated three dimensionally on the same radiograph as being upperface, midface and lowerface. The mean values were obtained for upperface, midface and lowerface. By making comparation of the mean values according to the mid sagital plain, it was indicated that upperface was almost symmetric while midface and lowerface were asymmetric.